Comparison of morphology and topography of surfaces of WEDM machined structural materials. (July 2017) - Mouralova, K.; Kovar, J.; Klakurkova, L.; Prokes, T.; Horynova, M.
Abstract: Wire Electric Discharge Machining (WEDM) is an unconventional machining technology using physical principles to cut materials. There are many factors affecting this process and having a fundamental influence on the final quality of the machined surface. Apart from the dielectric and wire electrode type used, these include, in particular, the machine setting parameters such as discharge current, gap voltage, pulse on and off time, and wire feed. Another very significant aspect of the machining process is mechanical and physical characteristics of the machined material including its heat treatment. This study deals with an analysis of morphology and topology of the surfaces of samples made of 4 structural materials and their 5 types of heat treatment. The analysis was carried out using electron microscopy (SEM) and a contact-less 3D profilometer which allowed evaluating the profile and surface parameters of surface quality including creating a 3D surface image.